SARS CoV-2: Epidemiology, Clinical Characteristics, Diagnosis, Therapeutics, Prevention and One Health Perspective with Reference to Meat Industry: 10.5958/2581-6616.2020.00018.3 - Barbuddhe, S.B.; Vergis, Jess; Malik, S.V.S.; Rawool, Deepak B. (Journal of Meat Science, 2020)
The coronavirus disease (COVID-19), a highly pathogenic viral infection caused by SARS-CoV-2, has caused global health concern. COVID-19 is closely related to severe acute respiratory syndrome (SARS) and the Middle East respiratory syndrome (MERS) and is a betacoronavirus. It is assumed that COVID 19 has zoonotic origin based on the large number of infected people who were exposed to the wet market in Wuhan City, China (Hamid et al., 2020). Bats could be the primary possible reservoir for the SARS-CoV-2 as it has shown significant sequence similarity with severe acute respiratory syndrome like (SARS-like) bat viruses. The intermediate host and their subsequent transfer are not known yet, although human to human transfer is widely confirmed. Identifying infected individuals to curb SARS-CoV-2 transmission has been challenging as compared to SARS and other respiratory viruses as the infected individuals can be highly contagious for several days before the appearance of symptoms (Anderson et al., 2020; He et al., 2020).
Keywords: (COVID-19); SARS-CoV-2; Clinical Characteristics; Diagnosis; Therapeutics